GE_GERICHTE P/12279/2023 vom 26. März 2024 - GE Cour de justice (2024)
LÉSION CORPORELLE PAR NÉGLIGENCE;DILIGENCE;ACCIDENT DE LA CIRCULATION;AUTOMOBILE;MOTOCYCLE LÉGER | CPP.3; CP.125; CP.12; LCR.26; LCR.31